2011
DOI: 10.1016/j.surfcoat.2011.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Protection of cobalt-based refractory alloys by chromium deposition on surface

Abstract: A high chromium content, typically 30wt.%, is generally considered as necessary for cobalt-based alloys to allow them resisting oxidation by hot gases. Cobalt alloys with a bulk poorer in chromium may become resistant against high temperature oxidation if they are enriched in chromium on surface. The aim of this second part of the work is to expose to air at 1200°C three low-chromium cobalt-based alloys (Co-10Cr, Co-10Cr-0.25C-4.4Ta and Co-10Cr-0.5C-8.7Ta in wt.%), previously enriched in chromium on surface by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It is possible to benefit from both high temperature strength and high oxidation resistance by decoupling the properties required for the bulk and for the surface, this by choosing a Co content high enough for the bulk to stabilize the TaC carbides and by enriching the outer part of the alloy in chromium. Recent work precisely demonstrated that this is precisely possible for TaC‐containing Cr x C y ‐free Cr rich {cobalt, nickel}‐based alloys with significant improvement of the high temperature oxidation behavior when the Cr content obtained in subsurface is 30 wt% . The thermodynamic calculations carried out in the present work showed that such resulting enrichment did not induce any serious problem for the microstructure of the Cr‐enriched outer zone.…”
Section: Resultssupporting
confidence: 61%
“…It is possible to benefit from both high temperature strength and high oxidation resistance by decoupling the properties required for the bulk and for the surface, this by choosing a Co content high enough for the bulk to stabilize the TaC carbides and by enriching the outer part of the alloy in chromium. Recent work precisely demonstrated that this is precisely possible for TaC‐containing Cr x C y ‐free Cr rich {cobalt, nickel}‐based alloys with significant improvement of the high temperature oxidation behavior when the Cr content obtained in subsurface is 30 wt% . The thermodynamic calculations carried out in the present work showed that such resulting enrichment did not induce any serious problem for the microstructure of the Cr‐enriched outer zone.…”
Section: Resultssupporting
confidence: 61%
“…This is also due to the interdendritic TaC carbides, which may facilitate the outward diffusion of chromium during oxidation as they facilitated its inward diffusion during cementation. 14 On the other hand, a C free Co based alloy was submitted to thermal cycling under conditions that mimic thixoforming of steels. The eutectic carbides, typical of Stellite alloys, are replaced in this alloy with Mo rich coarse secondary phase particles dispersed predominantly at interdendritic sites.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, such high Cr contents are to be avoided, even if high levels of chromium may be required in critical, hot corrosion problems in service (work in highly aggressive milieus). Surface and subsurface chromium enrichments, produced by the pack cementation process [18,19], for instance, can afford such high corrosion resistance without the loss of the necessary ductility and toughness at low and high temperatures.…”
Section: Discussionmentioning
confidence: 99%